Building a Religious and Innovative Organizational Culture: Transformative Leadership Practices of Madrasah Principals - Sriwahyuni, Eci; Syufyarma, Syufyarma; Nellitawati, Nellitawati (Lembaga Riset dan Inovasi Almatani, 2026)
Organizational culture plays a strategic role in supporting quality improvement and the sustainability of educational institutions, including madrasahs. The leadership of the madrasah principal is a key factor in shaping and directing organizational culture to align with religious values and the demands of educational innovation. This study aims to describe the transformational leadership practices of the madrasah principal in developing a religious and innovative organizational culture at MTsN 17 Tanah Datar. This research employed a qualitative approach with a case study design. The madrasah principal was selected as the key informant, while teachers and educational staff served as supporting informants selected through snowball sampling. Data were collected through observation, in-depth interviews, and document analysis. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checking. The findings indicate that the transformational leadership of the madrasah principal plays a significant role in transforming organizational culture from conventional work patterns into a religious, collaborative, innovative, performance-based, and externally oriented culture. This cultural transformation was realized through exemplary leadership and the strengthening of discipline, the habituation of religious activities as an organizational identity, the development of a participatory work culture, encouragement of innovation and continuous learning, the implementation of an appreciation-based culture, and the strengthening of communication and external relations of the madrasah. These changes in organizational culture have led to increased motivation and professionalism among madrasah members, improved institutional management quality, and a positive public image and community trust in the madrasah.